Chronic Illness Patients' Perceptions of Quality of Care During Hospitalization: A Qualitative Study - Afnan Tunsi PhD, MSc, BSN, RN; Raneem Alhelal BSN; Raneem Mujalled BSN; Erghad Alhadrami BSN; Rahaf Alsulami BSN; Aisha Alhofaian PhD, MSN, BSN, RN; Marym Alaamri PhD, MSN, BSN, RN; Lisa Babkair PhD, MSN, BSN, RN (SAGE Publishing, 2023)
Introduction The rising prevalence of patients living with chronic illnesses and frequent hospitalizations represent many challenges in delivering high-quality care. Assessing patients' perceptions and needs regarding the quality of health care services is a critical step in improving quality of care. Objective This study sought to explore the perception of quality of care from the perspectives and experiences of chronically ill patients during hospitalization. Methods This study was conducted using a qualitative descriptive design. Face-to-face semi-structured individual interviews were conducted with 15 chronically ill patients at their bedside during their current hospital admission. Analysis followed Braun and Clarke's thematic analysis approach. Results Overall patients were pleased with their hospitalization experience; however, they highlighted many aspects of care that can be addressed to improve the quality of care provided. Five themes were identified from the analysis as follows: defining quality of care; aspects related to the healthcare providers; unmet care needs; patient's involvement in healthcare decisions and care expectations and outcomes. Conclusion A key finding of this study was the association between quality of care and healthcare providers' skills, clinical competence, and attitudes. Poor communication and discoordination of care were the most significant impediment expressed. Actively involving patients in care may be effective when combined with meeting expectations. The findings of this study helped to identify the strength points and areas of improvement that are the cornerstone for developing tailored and patient-centered strategies to improve the quality of care during hospitalizations among chronically ill Saudis.